MASLAHAH AND STRATEGY TO ESTABLISH A SINGLE STATE-OWNED ISLAMIC BANK IN INDONESIA - Lucky Nugroho; Tengku Chandra Husnadi (Institute for Research and Community Empowerment (LPPM TAZKIA), 2016)
Objective - The market share of Islamic banking in Indonesia has continually decreased from 4.89% in 2013 to 4.85% in 2014 and 4.83% in 2015. As a result, the idea to establish a single state owned Islamic Bank occurs. This conceptual paper aims to contribute the maslahah framework regarding the future of Islamic banks in Indonesia.Methods - The methodology that used in this paper is a qualitative method which supported by quantitative data that align with the theory of the benefit of the Ummah (maslahah) and the community theory.Results - The breakthrough to increase the market share and deliver Indonesia becoming an Islamic financial hub is the option to convert the BRI as the biggest retail bank to a full fledge Islamic bank, and the next action is to acquire the Islamic banks which are subsidiary of conventional state-owned banks (Bank Syariah Mandiri-BSM, Bank Nasional Indonesia Syariah-BNIS, Bank Rakyat Indonesia Syariah-BRIS, and Bank Tabungan Negara Syariah-BTNS). Conclusions - Establishing a single state-owned Islamic bank is beneficial for the future of Islamic banks in Indonesia